Recovery of offline and online sentence processing in aphasia: Language and domain-general network neuroplasticity. (November 2019) - Barbieri, Elena; Mack, Jennifer; Chiappetta, Brianne; Europa, Eduardo; Thompson, Cynthia K.
Abstract: This paper examined the effects of treatment on both offline and online sentence processing and associated neuroplasticity within sentence processing and dorsal attention networks in chronic stroke-induced agrammatic aphasia. Twenty-three neurotypical adults and 19 individuals with aphasia served as participants. Aphasic individuals were randomly assigned to receive a 12-week course of linguistically-based treatment of passive sentence production and comprehension (N = 14, treatment group) or to serve as control participants (N = 5, natural history group). Both aphasic groups performed two offline tasks at baseline and three months following (at post-testing) to assess production and comprehension of trained passive structures and untrained syntactically related and unrelated structures. The aphasic participants and a healthy age-matched group also performed an online eyetracking comprehension task and a picture-verification fMRI task, which were repeated at post-testing for the aphasic groups. Results showed that individuals in the treatment, but not in the natural history, group improved on production and comprehension of both trained structures and untrained syntactically related structures. Treatment also resulted in a shift toward more normal-like eye movements and a significant increase in neural activation from baseline to post-testing. Upregulation encompassed right hemisphere regions homologs of left hemisphere regions involved in both sentence processing and domain-general functions and was positively correlated with treatment gains, as measured by offline comprehension accuracy, and with changes in processing strategies during sentence comprehension, as measured by eyetracking. These findings provide compelling evidence in favor of the contribution of both networks within the right hemisphere to the restoration of normal-like sentence processing patterns in chronic aphasia.